Using linear regression to establish empirical relationships - Marno Verbeek (IZA World of Labor, 2017)
Linear regression is a powerful tool for investigating the relationships between multiple variables by relating one variable to a set of variables. It can identify the effect of one variable while adjusting for other observable differences. For example, it can analyze how wages relate to gender, after controlling for differences in background characteristics such as education and experience. A linear regression model is typically estimated by ordinary least squares, which minimizes the differences between the observed sample values and the fitted values from the model. Multiple tools are available to evaluate the model.
Keywords: C1; C20; C51; C52; 330; linear regression; ordinary least squares; model specification; estimation and inference; causality